2007
DOI: 10.1017/s0021859607007551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolizable protein intake on rates of plasma leucine turnover and protein synthesis in heifers

Abstract: SUMMARYAn isotope dilution method using [1-13C]leucine (Leu) infusion together with open-circuit calorimetry was applied to determine the effect of metabolizable protein (MP) intake on rates of plasma Leu turnover and whole body protein synthesis (WBPS) in six heifers. WBPS rate was estimated from rate of plasma Leu turnover and Leu oxidation to carbon dioxide. The experiment consisted of three levels of MP intake and was conducted in a two 3×3 Latin square designs of three 21-day periods. The experimental die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This might be due to the fact that frozen garlic leaf retained more bioactive components than garlic leaf silage. Turnover of plasma amino acids and WBPS increased with increasing dietary energy and protein intake in ruminants (Fujita et al 2006;Sano et al 2008). Thus, Sano et al (2008) used different levels of CP intake in heifers and found that LeuTR and WBPS were significantly greater for the high CP intake group than for the low and medium CP intake groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be due to the fact that frozen garlic leaf retained more bioactive components than garlic leaf silage. Turnover of plasma amino acids and WBPS increased with increasing dietary energy and protein intake in ruminants (Fujita et al 2006;Sano et al 2008). Thus, Sano et al (2008) used different levels of CP intake in heifers and found that LeuTR and WBPS were significantly greater for the high CP intake group than for the low and medium CP intake groups.…”
Section: Discussionmentioning
confidence: 99%
“…Turnover of plasma amino acids and WBPS increased with increasing dietary energy and protein intake in ruminants (Fujita et al 2006;Sano et al 2008). Thus, Sano et al (2008) used different levels of CP intake in heifers and found that LeuTR and WBPS were significantly greater for the high CP intake group than for the low and medium CP intake groups. Fujita et al (2006) determined WBPS using the [ 2 H5]Phe model and reported that WBPS increased in response to increasing energy intake in adult goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…75 per h through the same catheter for 6 h. A blood sample (5 ml) was taken immediately before and four blood samples (5 ml) were taken at 30-min intervals during the last 90 min of [1-13 C]Leu infusion. Samples were transferred into centrifuge tubes containing heparin sodium and were chilled in ice until centrifugation (Sano et al 2004(Sano et al , 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, quantity and quality of diets and production rate or molar ratio of VFA in the rumen are closely related to intermediary metabolism in ruminants (Sutton et al 2003). To clarify the relationship, researches were conducted by changing sources of diets, roughage: concentrate ratio, and by providing VFA salt supplementation to diets and VFA infusion into the rumen (Harmon et al 1983;Gross et al 1990;Fujita et al 2006;Sano et al 2008). However, these methodologies involve in factors of different dietary sources, supplements or infusates.…”
Section: Introductionmentioning
confidence: 99%